2009
DOI: 10.7705/biomedica.v29i1.47
|View full text |Cite
|
Sign up to set email alerts
|

Ciclo de vida de Triatoma dimidiata Latreille, 1811 (Hemiptera, Reduviidae) en condiciones de laboratorio: producción de ninfas para ensayos biológicos

Abstract: Introducción. A pesar de la importancia de Triatoma dimidiata como vector de la enfermedad de Chagas, poco se conoce de su ciclo biológico y de la producción eficiente de insectos disponibles para ensayos biológicos. Objetivo. Determinar las características del ciclo de vida en el laboratorio y establecer las condiciones del estado nutricional para la producción eficiente de ninfas de V estadio para ensayos biológicos. Materiales y métodos. Se determinaron los tiempos de desarrollo de los estadios de ninfa en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
2
4
1
1
Order By: Relevance
“…Those differences in the potential number of vector-human contacts might help explain the greater incidence of human serological cases in the states of Michoacán and Oaxaca (>8,000 per year) compared with Morelos (<2,000 per year) (Ramsey et al 2003). Mortality rates were low and similar to those of some related triatomine species, such as T. maculata, Erichson, 1848, T. dimidiata Latreille, 1811, and M. longipennis (Feliciangeli and Rabinovich 1985, Reyes and Angulo 2009, Martínez-Ibarra et al 2012a) and to M. pallidipennis in a previous study (Martínez-Ibarra and Novelo-López 2004). Most of these species are considered to be important vectors of Chagas disease in their distribution areas (Salazar-Schettino et al 2010).…”
supporting
confidence: 81%
“…Those differences in the potential number of vector-human contacts might help explain the greater incidence of human serological cases in the states of Michoacán and Oaxaca (>8,000 per year) compared with Morelos (<2,000 per year) (Ramsey et al 2003). Mortality rates were low and similar to those of some related triatomine species, such as T. maculata, Erichson, 1848, T. dimidiata Latreille, 1811, and M. longipennis (Feliciangeli and Rabinovich 1985, Reyes and Angulo 2009, Martínez-Ibarra et al 2012a) and to M. pallidipennis in a previous study (Martínez-Ibarra and Novelo-López 2004). Most of these species are considered to be important vectors of Chagas disease in their distribution areas (Salazar-Schettino et al 2010).…”
supporting
confidence: 81%
“…However, it was observed that the duration of N3 was shorter in both groups. This reduction in the third stage was not observed in the cycles of T. arthurneivai (Juarez, 1970), T. dimidiata (Reyes & Angulo, 2009), T.carcavalloi (Cardozo-de-almeida et al, 2014), but it occurred with T.…”
Section: Discussioncontrasting
confidence: 54%
“…As for various previously studied triatomine species, such as Triatoma brasiliensis Neiva, Triatoma dimidiata (Latreille) and Triatoma ryckmani Zeledón and Ponce (Daflon-Texeira et al 2009, Reyes & Angulo 2009, Zeledón et al 2010, Reyes-Novelo et al 2011, the egg eclosion rate was greater than 70% for two of the three species studied, the exception being T. recurva. All of the species studied had average incubation periods of approximately 19 days, reflecting the favourability of the maintenance conditions for the development of these species.…”
Section: Discussionmentioning
confidence: 99%